The physical and mental health of a large military cohort: baseline functional health status of the Millennium Cohort - Engel Charles C; Wells Timothy S; LeardMann Cynthia A; Riddle James R; Smith Besa; Zamorski Mark; Smith Tyler C; Hoge Charles W; Adkins Joyce; Blaze Dan (BMC, 2007)
Abstract Background: The US military is currently involved in large, lengthy, and complex combat operations around the world. Effective military operations require optimal health of deployed service members, and both mental and physical health can be affected by military operations. Methods: Baseline data were collected from 77,047 US service members during 2001-2003 as part of a large, longitudinal, population-based military health study (the Millennium Cohort Study). The authors calculated unadjusted, adjusted, and weighted means for the Medical Outcomes Study Short Form 36-item Survey for Veterans physical (PCS) and mental component summary (MCS) scores over a variety of demographic and military characteristics at baseline. Results: The unadjusted mean PCS and MCS scores for this study were 53.4 (95% confidence interval: 53.3-53.4) and 52.8 (95% confidence interval: 52.7-52.9). Average PCS and MCS scores were slightly more favorable in this military sample compared to those of the US general population of the same age and sex. Factors independently associated with more favorable health status included male gender, being married, higher educational attainment, higher military rank, and Air Force service. Combat specialists had similar health status compared to other military occupations. Having been deployed to Southwest Asia, Bosnia, or Kosovo between 1998 and 2000 was not associated with diminished health status. Conclusion: The baseline health status of this large population-based military cohort is better than that of the US general population of the same age and sex distribution over the same time period, especially in older age groups. Deployment experiences during the period of 1998-2001 were not associated with decreased health status. These data will serve as a useful reference for other military health studies and for future longitudinal analyses.